Use of fungi for the bioconversion of rice straw into cellulase enzyme - Khan, Munir H.; Ali, S.; Fakhru'l-Razi, A.; Alam, Md. Zahangir (Taylor and Francis, 2007)
Cellulase production was carried out by solid state bioconversion (SSB) method using rice straw, a lignocellulosic material and agricultural waste, as the substrate of three Trichoderma spp. and Phanerochaete chrysosporium in lab-scale experiments. The results were compared to select the best fungi among them for the production of cellulase. Phanerochaete chrysosporium was found to be the best among these species of fungi, which produced the highest cellulase enzyme of 1.43 IU/mL of filter paper activity (FPase) and 2.40 IU/mL of carboxymethylcellulose activity (CMCase). The “glucosamine” and “reducing sugar” parameters were observed to evaluate the growth and substrate utilization in the experiments. In the case of Phanerochaete Chrysosporium, the highest glucosamine concentration was 1.60 g/L and a high concentration of the release of reducing sugar was measured as 2.58 g/L obtained on the 4th day of fermentation. The pH values were also recorded. The range of the pH was about 5.15 to 5.56 in the case of Phanerochaete Chrysosporium.